Perkembangan Kognitif Anak Selama Belajar Di Rumah - Iswantiningtyas, Veny (Universitas Nusantara PGRI Kediri, 2021)
Early childhood education has had a bad impact due to the Covid-19 pandemic. The government took a policy to conduct distance learning activities. In order for early childhood to retain their rights in the form of education, teachers and parents use a home learning approach. Parents play an important role in education as long as children learn at home, for example, to develop children's cognitive. One of the factors that influence cognitive development is the school environment. During this pandemic, almost all schools carry out teaching and learning activities using an online system, so that more or less it will affect the achievement of children's cognitive development. The purpose of this research was to determine the achievement of early childhood cognitive development during home study. This research is qualitative research with the subject of group B children at TK Kusuma Mulia Sidomulyo I Puncu Kediri, were in data collection using a cognitive development achievement assessment sheet involving teachers, the main reason researchers chose teachers was because researchers could not directly observe children about developmental achievements. cognitive. The filling out of the assessment sheet for the achievement of cognitive development carried out by the teacher based on the data obtained for 1 semester, the results of the study prove that during learning at home the achievement of children's cognitive development is still achieved.